2019
DOI: 10.1002/dmrr.3165
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of risk factors for amputation in diabetic foot infections

Abstract: Background Knowledge of risk factors is crucial to develop management and treatment protocols for the prevention of lower extremity amputation for patients with diabetic foot infections (DFIs). Methods We searched the research literature for studies reporting risk factors for lower extremity amputation in patients with DFI. The main outcome variables included both minor and major amputations. This study was reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐analyses (PRIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
92
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 41 publications
6
92
0
5
Order By: Relevance
“…Overall, Wagner grades were significantly correlated with the increased risk of amputation . A recent meta‐analysis demonstrated that Wagner Grades 4 (OR 4.3) and 5 (OR 6.4) were identified as predictors of amputation in DFU . It is rational that higher Wagner scores, especially grades 4 and 5, were strongly associated with amputation in the present study (OR 20.947) as Wagner grades 4 and 5 indicate the presence of localised or diffused gangrene because of ischaemia and infection.…”
Section: Discussionsupporting
confidence: 52%
“…Overall, Wagner grades were significantly correlated with the increased risk of amputation . A recent meta‐analysis demonstrated that Wagner Grades 4 (OR 4.3) and 5 (OR 6.4) were identified as predictors of amputation in DFU . It is rational that higher Wagner scores, especially grades 4 and 5, were strongly associated with amputation in the present study (OR 20.947) as Wagner grades 4 and 5 indicate the presence of localised or diffused gangrene because of ischaemia and infection.…”
Section: Discussionsupporting
confidence: 52%
“…Diabetic foot ulcers are a costly public health concern, with a large proportion leading to amputation or infection; DFUs are also associated with a reduced quality of life . The lifetime risk of developing a DFU is 15‐25% . However, once ulcerated, DFU recurrence rates are 40% within the first year and up to 65% after 5 years post‐healing .…”
Section: Introductionmentioning
confidence: 99%
“…Wound infection is a common and serious problem in patients with diabetes, and is admitted as a risk factor for lower extremity amputations, especially with multidrug-resistant infection (10)(11)(12). On the surface of ulceration, structured community of microbial cells would form a biofilm gradually to advance their own survival.…”
Section: Discussionmentioning
confidence: 99%